Ultracool dwarfs - Pavlenko, Ya.V. (Кинематика и физика небесных тел, 2005)
We present results of modelling of spectra of M-, L-, T-dwarfs. Theoretical spectra are fitted to observed spectra to study the main parameters of the low-mass objects beyond the bottom of the Main Sequence. Application of the “lithium” and “deuterium” tests for assessment of ultra-cool dwarfs is discussed.